PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN PADA HOTEL HORISON SEMARANG - Dira Puspita Sari, 14.05.51.0008; Soliha, Euis (Students' Journal of Economic and Management, 2019)
This study aimed to analyze the effect of service quality and price perception in the customer satisfaction and impact in the customer loyalty on the Hotel Horison Semarang. The sample in this study were 100 respondents. The sampling technique in this study using purposive sampling. Data were analyzed by using multiple linear regression analysis. The results showed that service quality and price perception have a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty. Service quality and price perception simultaneously have a positive and significant effect on customer satisfaction and customer loyalty.